Understanding and Improving the Care of Older Adults Living with Dementia Across Four Canadian Provinces during the COVID-19 Pandemic: A Mixed-Methods Study to Inform Policy and Practices - Vedel, Isabelle; Arsenault-Lapierre, Geneviève; Bergman, Howard; Bronskill, Susan; Couturier, Yves; Godard-Sebillotte, Claire; Henein, Mary; Kosteniuk, Julie; Khanassov, Vladimir; McAiney, Carrie; Morgan, Debra; O’Brien, Nadia; et al. (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: The implications of the COVID-19 pandemic are far reaching for persons living with dementia (PLWD) in the community and in long-term care (LTC), as they are among the most vulnerable. PLWD are at risk for severe COVID-19 and a disruption in accessing supportive and health care due to the confinement measures. Objectives: 1) To measure the impact of the pandemic on health and social services use, mortality, COVID-19 infection where possible of PLWD both in the community and in LTC facilities compared to before the pandemic; 2) To understand PLWDs’ and care partners’ perceived needs, behaviours related to health service use and the experiences of PLWD, care partners, and physicians with health and social services; 3) To generate and disseminate evidence-based and actionable recommendations on effective strategies to address the current pandemic and prepare for subsequent waves. Methods: A convergent mixed-methods design with a participatory approach in 4 Canadian provinces. Objective 1 will use a retrospective observational cohort design to examine administrative health data. Outcomes will include mortality (all-cause; COVID-19 related), health service use and, where possible, infection rates. Objective 2 will use an explanatory multiple case study, with surveys and semi-structured interviews to explore the experiences of PLWD and care partners using health and social services and the role of sociodemographic factors. The third, knowledge translation objective will integrate these results using a deliberative dialogue with key stakeholders (decision-makers, healthcare managers, PLWD, care partners, and clinicians) to develop and disseminate evidence-based recommendations for practice and policy. Impact and conclusion: This project will provide an understanding of the impact of the COVID-19 pandemic on PLWD and care partners in Canada and highlight areas for improvement.